Preoperative Opioid Use Is Associated with Early Revision After Total Knee Arthroplasty: A Study of Male Patients Treated in the Veterans Affairs System. (4th January 2017) - Ben-Ari, Alon; Chansky, Howard; Rozet, Irene
Abstract : Background: Opioid use is endemic in the U.S. and is associated with morbidity and mortality. The impact of long-term opioid use on joint-replacement outcomes remains unknown. We tested the hypothesis that use of opioids is associated with adverse outcomes after total knee arthroplasty (TKA). Methods: We performed a retrospective analysis of patients who had had TKA within the U.S. Veterans Affairs (VA) system over a 6-year period and had been followed for 1 year postoperatively. The length of time for which an opioid had been prescribed and the morphine equivalent dose were calculated for each patient. Patients for whom opioids had been prescribed for >3 months in the year prior to the TKA were assigned to the long-term opioid group. A natural language processing-based machine-learning classifier was developed to classify revisions due to infectious and non-infectious causes on the basis of the postoperative note. Survival curves for the time to knee revision or manipulation were used to compare the long-term opioid group with the patients who did not take opioids long-term. Hazard and odds ratios for knee revision and manipulation were obtained as well. Results: Of 32, 636 patients (94.4% male; mean age [and standard deviation], 64.45 ± 9.41 years) who underwent TKA, 12, 772 (39.1%) were in the long-term opioid group and 734 (2.2%) had a revision within a year after the TKA. Chronic kidney disease, diabetes, and long-term opioid use were associated with revision within 1 year—with odds ratios (95% confidence intervals [CIs]) of 1.76 (1.37 to 2.22), 1.11 (0.93 to 1.31), and 1.40 (1.19 to 1.64), respectively—and were also the leading factors associated with a revision at any time after the index TKA—with odds ratios (95% CIs) of 1.61 (1.34 to 1.92), 1.21 (1.08 to 1.36), and 1.28 (1.15 to 1.43), respectively. Long-term opioid use had a hazard ratio of 1.19 (95% CI = 1.10 to 0.24) in the analysis of its relationship with knee revision, but the hazard was not significant in the analysis of its association with knee manipulation. The accuracy of the text classifier was 0.94, with the area under the receiver operating characteristic curve being 0.99. There was no association between long-term use of opioids and the specific cause for knee revision. Conclusions: Long-term opioid use prior to TKA was associated with an increased risk of knee revision during the first year after TKA among predominantly male patients treated in the VA system. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.